Taxonomy of ‘Euconnus complex'. Part XXV. Afrotropical species misplaced in Magellanoconnus Franz transferred to Euconnus Thomson (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2025)
Twenty-nine species of Afrotropical Stenichnini occurring in the Republic of South Africa and Zimbabwe and previously misplaced in Magellanoconnus Franz are transferred to Euconnus Thomson, subgenus Tetramelus Motschulsky.